Trace-metaldynamics in response of increase CO2 and iron availability in a coastal mesocosm experiment - Lorenzo, M. Rosario; Maldonado, Maria T.; Lázaro, Francisco J.; Cullen, Jay T.; Segovia-Azcorra, María (My University, 2015)
A mesocosm experiment was performed in the Raunefjord (Norway) to study changes in dissolved Cu (dCu) and Fe (dFe), and in the elemental composition of particles during an Emiliania huxleyi dominated bloom. The CO2 treatments consisted of present (LC; 390 ppmV) and predicted levels (HC; 900 ppmV) and iron conditions were created with the addition of the siderophore desferoxamine B (DFB). Our results showed the DFB addition enhanced the solubility of Fe in this fjord environment. Initially, dFe was comparable among treatments but after the addition, the HC and/or +DFB treatments presented higher levels and finally, the only ones maintaining high dFe were the +DFB treatments. Unlike dCu presented indistinguishable levels in all mesocosms over time. Particulate metals were normalised to P and Al to evaluate the relative influence of biotic and abiotic sources. The Fe:P ratios decreased with time and compared to published phytoplankton ratios suggest Fe storage. On the other hand, Fe:Al ratios were relatively closer to the crustal ratios suggesting that the abiotic source was more important for this metal. Trends for other metals will be discussed.
Keywords: Fitoplancton marino; Marine biology; Phytoplankton; CO2; Iron; Mesocosm